Microwave Assisted Solvent Extraction Study of Ficus Exasperata (Vahl) Stem Bark Antimicrobial Potential Agaisnt Methicillin - Ibrahim Jimoh; Usman M.T; Sulle M.O (Genius Journals, 2021)
Stem bark of Ficus exasperata was extracted using ethyl acetate by microwave-assisted solvent extraction. Phytochemical screening and antimicrobial evaluation were carried out on the extract. Phytochemical screening revealed the presence of cardiac glycosides, tannins, flavonoids, triterpenes and steroids. Antimicrobial evaluation revealed that the extract is active against Methicillin – resistant Staphylococus aureus (MRSA), Staphylococcus aureus, Streptococcus pneumoniae, Salmonella typhi, Proteus mirabilis, Shigella dysenteriea, Candida stellatoidea and Candida tropicalis. The zones of inhibition (mm) for the test organisms were 27, 30, 31, 26, 27, 29, 27and 24 respectively. Minimum inhibition concentrations (mg/L) of extract against Methicillin – resistant Staphylococus aureus (MRSA), Staphylococcus aureus, Streptococcus pneumonia, Salmonella typhi, Proteus mirabilis, Shigella dysenteriea, Candida stellatoidea and Candida tropicalis were 2.5, 1.25, 1.25, 2.5, 1.25, 1.25, 1.25 and 2.5 respectively. Minimum bactericidal/fungicidal concentrations (mg/L) of extract against Methicillin – resistant Staphylococus aureus (MRSA), Staphylococcus aureus, Streptococcus pneumonia, Salmonella typhi, Proteus mirabilis Shigella dysenteriea Candida stellatoidea and Candida tropicalis were 5,2.5,2.5,5,5,2.5,2.5 and 5 respectively
Keywords: Antimicrobial evaluation; Minimum Inhibition Concentration; Microwave; Phytochemical screening